2020
DOI: 10.1021/acs.inorgchem.0c01572
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the “Absent” Vanadium Oxo V(═O){N(SiMe3)2}3, Imido V(═NSiMe3){N(SiMe3)2}3, and Imido-Siloxy V(═NSiMe3)(OSiMe3){N(SiMe3)2}2 Complexes Derived from V{N(SiMe3)2}3 and Kinetic Study of the Spontaneous Conversion of the Oxo Complex into Its Imido-Siloxy Isomer

Abstract: The synthesis and characterization of V(O){N(SiMe 3 ) 2 } 3 (1), V(NSiMe 3 ){N(SiMe 3 ) 2 } 3 (2), and V(NSiMe 3 )(OSiMe 3 ){N(SiMe 3 ) 2 } 2 (3) are described. Prior attempts to synthesize the vanadium(V) oxo complex 1 via salt metathesis of VOCl 3 with the lithium or sodium silylamide salt had yielded either the putative rearranged species V(NSiMe 3 )(OSiMe 3 ){N(SiMe 3 ) 2 } 2 (3) or the oxo-bridged, dimetallic {(μ-O) 2 V 2 [N(SiMe 3 ) 2 ] 4 }. We now show that complex 1 is available by treatment of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 75 publications
(147 reference statements)
0
3
0
Order By: Relevance
“…A coordination chemistry was initiated for the titanium and vanadium tris­(silylamide) complexes (previously thought not possible due to steric crowding) to give M­{N­(SiMe 3 ) 2 } 3 L 2 (L = a nitrile or isocyanide ligand) complexes . Additionally, the isolation of a new vanadium­(V) oxy silylamide complex, e.g., V­(=O)­{N­(SiMe 3 ) 2 } 3 , that was absent from the literature despite several attempts to isolate it, and the synthesis of several unusual metal hydride complexes that are available by reduction of M­{N­(SiMe 3 ) 2 } 3 complexes were described …”
Section: Introductionmentioning
confidence: 99%
“…A coordination chemistry was initiated for the titanium and vanadium tris­(silylamide) complexes (previously thought not possible due to steric crowding) to give M­{N­(SiMe 3 ) 2 } 3 L 2 (L = a nitrile or isocyanide ligand) complexes . Additionally, the isolation of a new vanadium­(V) oxy silylamide complex, e.g., V­(=O)­{N­(SiMe 3 ) 2 } 3 , that was absent from the literature despite several attempts to isolate it, and the synthesis of several unusual metal hydride complexes that are available by reduction of M­{N­(SiMe 3 ) 2 } 3 complexes were described …”
Section: Introductionmentioning
confidence: 99%
“…These were first reported in the early 1960s by Bürger and Wannagat , and later studied extensively by Bradley and co-workers. Currently, three-coordinate transition metal M­{N­(SiMe 3 ) 2 } 3 complexes are known for the first row metals from scandium through cobalt, , several lanthanides, ,− as well as plutonium and uranium. , Our recent finding that the complex V­{N­(SiMe 3 ) 2 } 3 had been initially mischaracterized in the 1970s ,, led us to reexamine first-row transition metal M­{N­(SiMe 3 ) 2 } 3 complexes. Advances in techniques for the handling and characterization of such complexes has allowed the development of the coordination chemistry for the titanium and vanadium tris­(silylamide) complexes, as well as the isolation of several high-valent vanadium complexes that were unknown despite earlier efforts to synthesize them. As described in these reports, attempts to extend this chemistry to other first-row transition metal M­{N­(SiMe 3 ) 2 } 3 complexes (M = Cr, Mn, Fe, Co) were largely unsuccessful. However, isolation of the chromium­(II) complex [K­(18-crown-6)­(Et 2 O) 2 ]­[Cr­{N­(SiMe 3 ) 2 } 3 ] by reduction of Cr­{N­(SiMe 3 ) 2 } 3 suggested that the later metal tris­(silylamide) complexes may be useful synthons for lower valent species …”
Section: Introductionmentioning
confidence: 99%
“…Most prominent examples among the bis­(trimethylsilyl)­amido complexes are two coordinate complexes such as [Fe­{N­(SiMe 3 )­(Dipp)} 2 ] (dipp = C 6 H 3 -2,6- i Pr 2 ). , But also three coordinate iron­(II/III), cobalt­(II), and nickel­(I) complexes, i.e., [M­{N­(SiMe 3 ) 3 } 2 L] (M = Fe, Co; L = ligand), [Fe­{N­(SiMe 3 ) 3 } 3 ], , and [Ni­(N­(SiMe 3 ) 2 )­(PPh 3 ) 2 ] and four-coordinate chromium­(II) complexes [Cr­(N­(SiMe 3 ) 2 ) 2 (L) 2 ] (L = py, thf) attracted some attention . One further important aspect is studies of the coordination behavior of these coordinatively unsaturated compounds, a situation which also enables them to activate small molecules. Finally, basic aspects like optimization of existing synthetic protocols including the synthesis of new compounds are still an actual and common interest like evidenced by some recent papers. …”
Section: Introductionmentioning
confidence: 99%